THE RIPPLE EFFECT OF WORK FAMILY CONFLICT: EXAMINING PARENTING STRESS IN DUAL-EARNER FAMILIES WITH SCHOOL-AGED CHILDREN - Rizal, Gumi Langerya; Govindasamy, Priyalatha; Fikry, Zulian; Duryati, Duryati (Program Studi PGMI, 2024)
Balancing work and family life is a significant challenge for dual-earner families, particular-ly for parents with elementary school-aged children. This study investigates the cross-relationship between work-family conflict (WIF and FIW) experienced by husbands and par-enting stress experienced by wives in dual-earner families. Utilizing a quantitative survey de-sign, data were collected from 246 dual-earner couples with school-aged children. The find-ings reveal that WIF experienced by husbands significantly increases the parenting stress of wives, while FIW experienced by husbands does not show a significant effect. These results highlight the importance of considering the interactive dynamics within dual-earner families and the need for supportive measures to mitigate the negative impacts of work-family conflict on overall family well-being.